Efeitos colaterais da isoniazida: relato de caso - Paula Silva Almada; Rafaela Baroni Aurilio; Maria de Fatima Pombo Sant'Anna (Sociedade Brasileira de Pediatria, 2022)
Treatment of latent tuberculosis infection (LTBI) is an important preventive measure and deserves international interest. Although other LTBI treatment regimens exists, the use of isoniazid is established. The present case report is of a 9-year-old boy with asthma and epilepsy who presented adverse reactions to the use of isoniazid prescribed as a therapy for ILTB. After withdrawing the drug that was replaced by rifampicin, the patient showed clinical improvement.